Pemanfaatan Aplikasi Google Form Sebagai Media Ujian Online Seleksi Karyawan Baru PT Indeks Media Teknologi Pada Era Pandemi - Ita Arfyanti; Nursobah Nursobah (JPM: Jurnal Pengabdian Masyarakat, 2021)
The era of the pandemic or a situation in which many countries have locked down in various regions due to the spread of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) or the covid-19 virus and caused a lot of economic chaos due to the long suspension of activities that led to ordered by the government to break the chain of the spread of the virus, the pandemic era caused many companies to go out of business and led to an increase in the number of unemployed. PT Indeks Media Teknologi is one of the companies that is developing in distributing and producing goods in the form of equipment and gas cylinder safety which is widely used by the community, the high number of unemployed in the pandemic era, has led to a high rate of submission of job applications to companies, especially the private company PT Indeks Media Teknologi. The selection of employee recruitment certainly has certain requirements, one of which is by giving prospective employees several written knowledge exams to see the prospective employees according to the needs of the company, this can be done by using online media to provide access to prospective new employees in taking the exam so that the the company did not violate the provisions of the lockdown. One application that can be used as an online exam provider facility is Google Form where this application is a feature provided by Google for free by having various models and types of exam methods. Through the provision of training on the benefits of using google forms, PT Indeks Media Teknologi was able to solve problems in the difficulty of recruiting new employees in giving written exams during the pandemic era